Colouring perception: Package colour cues affect neural responses to sweet dairy drinks in reward and inhibition related regions. (1st November 2019) - Tijssen, Irene O.J.M.; Smeets, Paul A.M.; Goedegebure, Robert P.G.; Zandstra, Elizabeth H.; de Graaf, Cees; Jager, Gerry
Abstract: Extrinsic product cues such as package colour may change product perception and perceived reward value during product evaluation. Healthier foods ( i.e., 'light', sugar- or fat-reduced) often have different packages than regular products, e.g., they may be less vibrantly coloured. People vary in their degree of health-interest and self-control ability and may be affected differently by package colour. This study assesses the extent to which package colour and participant characteristics interact and influence product perception and brain responses. Thirty-four healthy females performed a functional MRI task in which they viewed four differently coloured packages (regular vs. healthier; differing in brightness and saturation levels) with or without simultaneously tasting a either a regular or a healthier calorie-reduced drink. Results indicate main effects of package and taste and a package*taste interaction effect. Compared to healthier packages viewing regular packages enhanced activation in region implicated in inhibitory control (inferior frontal gyrus) and a reward-related region (striatum), the latter even more so as participants' health interest increased ( r = 0.43, p = 0.01). Incongruent package-taste combinations decreased activation in the orbitofrontal cortex (OFC, a region implicated in reward representation) compared to congruent combinations. Tasting the healthier compared to regular product enhanced activation in the middle and superior frontal gyrus, which are implicated in inhibitory control, as well as the striatum and OFC, suggesting a cognitively driven preference for the healthier product. In conclusion, this paper provides evidence for the conditions under which package colour and taste properties modulate neural correlates related to reward and inhibition. Individual differences in health-interest and impulsivity influence package- and taste-related neural correlates and thus underscore the importance of taking participant characteristics into account in food research.